Sustainability of Current Account Deficit in Turkey (1989–2014) - Zubeyir Turan; Doğan Barak; Ayberk Nuri Berkman; Aslıhan Nakiboglu (International Journal of Economics and Financial Issues, 2016)
The current account deficit, as a frequently disputable phenomenon of Turkish economy, is considered as one of the main causes of the crises in the economy. The current account deficit is one of the important problems in some developed countries as well as in developing countries. Indeed, the long-term sustainability of such an incident which results from expenditures in excess of the income or investments in excess of the savings in a country is subject to discussion. Despite its experience of a rapid process of change following the decisions of 24th January 1980, The Turkish banking sector has been severely damaged during the crisis of November 2000 and February 2001 in particular. The global financial crisis of the year 2008, like the rest of the world, has also increased uncertainties in Turkey along with a reduction in demand, a decline in production which, in turn, led to the emergence of negative impacts on the real and financial sectors. The aim of this study is to examine the sustainability of current account dcflcit in Turkey between the years 1989 – 2014. The technical analysis conducted with the econometric model is also supported by a variety of data analysis.